# ALGEBRA

posted by .

1+2x+6x^2+9x^3+7-2x+6x^2-9x^3...
won't I have to combine terms & then get
8+12x^2

cause won't the 9x^3 and the 2x cancel itself out???

• ALGEBRA -

You can only add/subtract "like" terms, that is, you can add x^3's to x^'s, x's to x's etc.

so yes, you are right.

• ALGEBRA -

thanks!!!

## Similar Questions

1. ### Simplifying Rational Expressions

1.4x12 / 4x 2.d+7 / d^2-49 3.t^2-25 / t^2+t-20 4.2x^2+6x+4 / 4x^2-12x-16 5.6-y / y^2-2y-24 1. 12 [4x] cancels out. so you're left with just 12. 2. 1/d-7 factor the d^2-49 to (d+7)(d-7). cancel out the (d+7) 3. (t-5)/(t-4) factor both …
2. ### Maths

you have to solve the following by finding the value of x and y. can u help please?
3. ### Algebra

2(3x - 7) + 4 (3 x + 2) = 6 (5 x + 9 ) + 3 how will solve it?
4. ### maths

Can someone please help me with solving this equation (I don't know how to do it with the fractions) 1/3 x1^-2/3 . x2^2/3 -------------------- 2/3 x1^1/3 . x2^-1/3 how do I cancel out some of the terms and reduce it down so that Im …
5. ### intermediate algebra

Write the equation of the line containing (-3,4) and perpendicular to y = 2/3x + 2. Write your answer in slope-intercept form. Not sure how to do this one. m = -3/2 y = mx + b y - 4 = -3/2 (x-4) am i on the right track?
6. ### algebra

5x -3 = 11 + 12x combine like figures add 3 to both sides to remove the 3 5x= 14+ 12x Now I get confused. If I remove the 12x I have to subtract 12x from 5x which gives me an answer of -7x=14 would the correct answer thus be x= -2?
7. ### Algebra

combine the like terms -9x - 13x = 12x
8. ### Algebra

combine like terms -9x - 13x + 7 easy problem My professor says I have an error in combine "x" terms -22x + 7 help!
9. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17
10. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17

More Similar Questions